Electronic‐photonic board as an integration platform for Tb/s multi‐chip optical communication. Issue 2 (3rd March 2021) - Lamprecht, Tobias; Betschon, Felix; Bauwelinck, Johan; Van Kerrebrouck, Joris; Lambrecht, Joris; Gaul, Holger; Eichler, Alexander; Yin, Xin
Abstract: Chip‐on‐board silicon photonics O‐band wavelength‐division multiplexing transceivers have been developed that will eventually enable high‐throughput on‐board optical communication for multi‐socket on‐board communication. This direct, any‐to‐any configuration yields low‐latency, low‐power optical communication among multiple compute nodes on the board. Silicon photonic transceiver chips are flip‐chipped on a polymer waveguide containing an electro‐optical circuit board using adiabatic coupling and then completed with driver and amplifier electronic chips. A transceiver assembly based on wire‐bond technology verifies 50 Gb/s operation per channel, and the flip‐chip version demonstrates the chip on‐board assembly techniques for compact on‐board transceivers.